Preparation methods of membrane electrode assemblies for proton exchange membrane fuel cells and unitized regenerative fuel cells: A review. (November 2020) - Bhosale, Amit C.; Ghosh, Prakash C.; Assaud, Loïc
Abstract: Hydrogen technologies will become more prominent in the next coming years, in particular systems operating at close to ambient temperature, in the context of sustainability and renewable energies. Membrane electrode assembly (MEA) has been the most primary part of the conventional polymer electrolyte fuel cells as well as unitized regenerative fuel cells. This paper summarizes the important steps and latest developments in the preparation of the assembly such as membrane treatment, preparation of electrodes followed by hot pressing for low temperature (<100 °C) polymer electrolyte fuel cells and unitized regenerative fuel cells. Various possibilities in the membrane selection for the assemblies are detailed out and their performances are compared with respect to the preparation methods. Catalysts play a very important role in supporting oxygen reduction as well as evolution reaction and primarily differentiate the MEAs of the cells. Hence, they are tabulated along with the possible supports. Also, importance of wet proofing the gas diffusion backing along with preparation of microporous layer with different materials and processes is also reviewed. Hot pressing which is conventionally used for preparing the assemblies makes a great difference when used with optimized operating parameters such as pressure, temperature and time during the pressing. A comparison between the various techniques used for MEA fabrication is summarized and is believed to be useful for researchers. In addition to an extended review on the preparative techniques for MEA manufacturing, the authors underline the performance of a unitized regenerative fuel cell (area = 22.5 cm 2 ) by incorporating the salient steps involved during the preparation of membrane electrode assemblies. Highlights: Possible varieties of membranes used commercially are summarized. New as well as commercial catalysts including catalyst base are detailed out. Various gas diffusion layers and microporous layers along with their preparation methods are discussed. Governing parameters during conventional hot press method are summarized along with characterization of a single URFC cell (area: 22.5 cm 2 ).